PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK BERTUKAR PASANGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 2 BAYANG TAHUN PELAJARAN 2012/2013 - Dianti, Elfira; Rismen, Sefna; Husna, Husna (STKIP PGRI Sumbar, 2013)
The research was motivated by difficulties of studentsâ comprehension of the material individually or studentsâ math concept at eightÂ grade of SMPN 2 Bayang that apply cooverative learning Change Pair technigue better than studentsâ comprehensionÂ of math concept that apply conventional learning. The type of research is experimental by using Randomized Control Group Only Design.Â The data analysis technique used is T-Test . Techniques of data analysis were performed using one-way t test. Based on the analysis of data obtained t of 4.95 is greater than the amount specified t table 1.64. Then the hypothesis in this research received. In conclusion, studentsâ comprehension of math concept that apply cooperative learning Change Pair technigue better than studentsâ comprehension of math concept that apply conventional learning.